Pengembangan Strategi Pemasaran Buah Jeruk untuk Meningkatkan Penjualan dan Kesejahteraan Masyarakat - Adi Sofyana Latif; Rananda Septanta; Khuzaeni Khuzaeni; Ahmad Syauqi (Jurnal PKM Manajemen Bisnis, 2026)
The marketing of citrus fruit products in local communities faces challenges related to limited promotion strategies and low consumer awareness which impact sales performance and community welfare especially in small scale community based agricultural marketing in rural settings contexts. Objective: This community service program aims to develop effective citrus fruit marketing strategies to increase sales and improve the welfare of the community through training and community engagement activities and sustainable development goals. Methods: The PKM activity was conducted at the Pamulang Orphan and Yatim Foundation in South Tangerang on April 11, 2026, involving five lecturers from Universitas Pamulang and 23 participants consisting of children and teachers from the orphanage foundation using presentation practice discussion and question and answer methods through preparation implementation and reporting stages and interactive evaluation to ensure effective understanding with pre and post evaluation assessments of knowledge gain results. Results: The program increased participants' understanding of marketing concepts and practical skills in promoting citrus products fostering enthusiasm for entrepreneurship and contributing to potential improvements in sales and community welfare leading to increased motivation among participants demonstrating improved marketing awareness practical application skills in real contexts.